The A to Z history of London - Parker, Philip 1965- (Collins, 2019)
For the last century A-Z maps have been the trusted and reliable source of mapping for Londoners. As the face of London has changed so have the maps. This book outlines these changes and reveals how the city has changed over the last one hundred years. Did you know that Wembley Stadium used to be a Greyhound racing circuit? The Millennium Dome is the biggest structure of its kind in the world? The London Eye was not the first big wheel in London. London's skyline has gone from Big Ben and Tower Bridge to include the Tate Modern and The Shard. Several ill-fated projects appeared on maps, including London Millennium Tower and The Sparkplug, which never quite made it into the city's skyline
Includes index
Keywords: Geschichte 1936-2019; Historische Kartografie; Stadtplan; Stadtbild; London; London (England) / Historical geography / Maps; London (England) / History / Maps; Historical geography; England / London; History; Maps